Analysis of The Impact of Financial Statements Based on PSAK 101 In Maintaining Business Stability - Aisyah; Ahmad Abdul Mutalib; Jumarni (Institut Pendidikan Alfatah Mataram, 2025)
This research analyzes the impact of financial reporting based on PSAK 101 on business stability at Karya Ilmu Book Business. PSAK 101 is an accounting standard for sharia entities emphasizing transparency and accuracy in financial statements. Using qualitative methods with a case study approach, data was collected through observation, interviews, and documentation. Results indicate that PSAK 101 has not been fully implemented, with financial statements still prepared manually and not structured according to standards. This condition leads to a lack of transparency in financial management that can affect business stability, especially in facing competition and strategic decision-making. The research emphasizes the importance of implementing PSAK 101 to improve operational efficiency and stability of MSMEs. The research findings are expected to serve as a reference for business actors in improving financial recording systems and for policymakers in supporting sharia accounting regulations for MSMEs.